2017
DOI: 10.4103/jpn.jpn_158_16
|View full text |Cite|
|
Sign up to set email alerts
|

Magnitude of neurogenic tumor burden in pediatric population: A tertiary care center study

Abstract: Objective:Progress in the diagnosis and treatment of childhood neoplasm in the past few decades is one of the most gratifying achievements in the field of oncology. This study was aimed to ascertain the burden (incidence and prevalence) and histopathologic features of neurogenic tumors occurring in the pediatric population.Materials and Methods:The study evaluated a total of 492 cases of pediatric tumors over a period of 8 years from 2007 to 2015, including patients of 0–12 years of age group; attending the ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
3
1
0
Order By: Relevance
“…Most of the previous study had reported infratentorial region as the commonest site for pediatric astrocytic tumors. 5 However, few studies are consistent with our study and had reported that supratentorial region predominate slightly for these astrocytic tumors in children. 6 Most of the studies had reported that cerebellum was the commonest site for these tumors, which is also consistent with our study.…”
Section: Discussionsupporting
confidence: 92%
“…Most of the previous study had reported infratentorial region as the commonest site for pediatric astrocytic tumors. 5 However, few studies are consistent with our study and had reported that supratentorial region predominate slightly for these astrocytic tumors in children. 6 Most of the studies had reported that cerebellum was the commonest site for these tumors, which is also consistent with our study.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, embryonal tumors are the most common histology type, followed by astrocytomas, schwannomas, and least common type is of mixed gliomas and ependymomas. Prevalence of Medulloblastoma is similar to that observation by Jain et al 2011 and Qadri et al, 2017 [8,12] where its account for more than 30%. Of these medulloblastoma cases, males (n=8) are more predominant than females (n=3) (table 2).…”
Section: Discussionsupporting
confidence: 89%
“…Under this histological type, pilocytic astrocytoma was commonly followed by diffuse astrocytoma. Our results are comparable to [12,14], except anaplastic Astrocytomas. Astrocytomas were common in females (n=6) than males (n=2).…”
Section: Original Research Articlesupporting
confidence: 91%
“…In the article titled ‘Magnitude of Neurogenic tumor burden in Pediatric population: A Tertiary Care Centre Study’ published in the pages 222-226, Issue 3, Volume 12 (July-Sept 2017), of Journal of pediatric Neurosciences[ 1 ], the name of fourth Author: Rana K Sherwani, Professor D/O Pathology, Jawaharlal Nehru Medical College, is to be included as it was missed during submission of the article, although the author has a significant contribution in the study.…”
mentioning
confidence: 99%